The Effectiveness of Reciprocal Teaching Strategy to Increase Students Reading Comprehension in Narrative Text - Nurul Hikmah Islamiyah; Sulton Dedi Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
Reciprocal Teaching Strategy has proven as a good method in increasing students reading comprehension. This method has been applied in teaching in elementary school students, ESL (English as Second Language) and EFL (English as Foreign Language) contexts. The researcher doing a research about the implementation of Reciprocal Teaching Strategy to increase students reading comprehension. The objective of thisÂ research is to find out whether Reciprocal Teaching Strategy is Effective in Increasing Students Reading Comprehension in Narrative Text and to know how Reciprocal Teaching Strategy enhance studentsâ€™ reading comprehension in narrative text. This research use a quantitative method Quasi Experimental Design. The data is analyzed by the researcher using SPSS and Microsoft Excel. The subject are eighth grade one of the State Junior High School of Surabaya. This research done for about one month from 20th January until 22nd February 2018. Reciprocal Teaching Strategy has 4 steps in it, such as: Predicting, Questioning, Clarifying, and Summarizing. This strategy is effective for studentsâ€™ cognitive process in reading that prevent from failure and the result showed Reciprocal Teaching is Effective In Reading Narrative Text, it can be seen from the significant improvement of students score of pretest to post test.